Percepção dos alunos de uma instituição de ensino superior sobre o ensino do empreendedorismo - Silva, Maria Vitalina dos Santos (Brasil, 2024)
Entrepreneurship is increasingly assuming an important role in generating new businesses. With this in mind, the main objective of this research is to evaluate the perception of students in the business administration course about the teaching of entrepreneurship in a higher education institution in Amazonas. The chosen methodology consists of a quantitative and qualitative research with content analysis. The data were collected through a questionnaire with closed and open questions, which was answered by 37 university students. The main results obtained indicate that there are barriers in the promotion of practical content on entrepreneurship, a lack of direct interaction with professionals in the area and a lack of intensity in the dissemination of existing programs in the higher education institution. The respondents suggested the integration of mentoring programs regarding entrepreneurship and more dynamic disciplines. Therefore, the research reveals that, although the institution is on the right track in promoting an entrepreneurial culture, there are still actions that require significant improvements. If the institution implements the suggestions received, adopting a more practical approach connected to the market, it will be able to enhance the training of future entrepreneurs, who will be prepared to face the challenges of the contemporary job market and effectively contribute to the economic and social development of the region.